2011
DOI: 10.1007/s00408-011-9286-3
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab-based Therapy is Effective in Chemotherapy-naïve Patients with Advanced and Metastatic Non-small-cell Lung Cancer: A Meta-analysis of Randomized Controlled Trials

Abstract: Randomized controlled trails (RCTs) where cetuximab added to first-line platinum-based chemotherapy for patients with advanced/metastatic non-small-cell lung cancer (NSCLC) have yielded conflicting results. This meta-analysis intended to evaluate the efficacy and safety of cetuximab-based therapy (CBT) in that setting. We analyzed four eligible RCTs that included 1,003 and 1,015 patients randomized to CBT and control intervention, respectively. As compared with the noncetuximab group, CBT demonstrated an 9% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Panitumumab is a fully human immunoglobulin G2 monoclonal antibody directed against EGFR, which showed survival benefits in OS and PFS in gastric cancer and advanced colorectal cancer (Douillard et al, 2010a;Waddell et al, 2013). Cetuximab is a chimeric monoclonal antibody that binds to the EGFR and blocks the EGFR signaling cascade, producing significant clinical benefit with acceptable toxicity in patients with advanced/metastatic non-small cell lung cancer (NSCLC) (Mendelsohn et al, 2003;Ibrahim et al, 2011), while results showed no significant benefit of OS (HR 1.00; 95% CI 0.87-1.1; p=0.95) and PFS (HR 1.09;p=0.32)in the intention-to-treat population with advanced gastric cancer (Lordick et al, 2013). Matuzumab is a humanized anti-EGFR monoclonal antibody (anti-EGFR MoAb).…”
Section: Meta-analysis Of Six Randomized Control Trials Of Chemotheramentioning
confidence: 99%
“…Panitumumab is a fully human immunoglobulin G2 monoclonal antibody directed against EGFR, which showed survival benefits in OS and PFS in gastric cancer and advanced colorectal cancer (Douillard et al, 2010a;Waddell et al, 2013). Cetuximab is a chimeric monoclonal antibody that binds to the EGFR and blocks the EGFR signaling cascade, producing significant clinical benefit with acceptable toxicity in patients with advanced/metastatic non-small cell lung cancer (NSCLC) (Mendelsohn et al, 2003;Ibrahim et al, 2011), while results showed no significant benefit of OS (HR 1.00; 95% CI 0.87-1.1; p=0.95) and PFS (HR 1.09;p=0.32)in the intention-to-treat population with advanced gastric cancer (Lordick et al, 2013). Matuzumab is a humanized anti-EGFR monoclonal antibody (anti-EGFR MoAb).…”
Section: Meta-analysis Of Six Randomized Control Trials Of Chemotheramentioning
confidence: 99%
“…While direct comparisons cannot be made, a recently published meta-analysis examined effectiveness of cetuximab-based therapy in chemotherapy-naive patients with advanced and metastatic NSCLC [30]. As compared to a non-cetuximab control group, cetuximab-based therapy demonstrated a 9% reduction in the risk of disease progression, a 13% reduction in the risk of death, and an approximately 50% increase in ORR.…”
Section: Discussionmentioning
confidence: 97%
“…Cetuximab has also shown efficacy in the treatment of non-small-cell lung cancer (NSCLC) [21][22][23][24][25]and locally advanced head and neck squamous cell carcinoma (HNSCC) [26,27].…”
Section: Monoclonal Antibodies To Target Egfrmentioning
confidence: 99%